Analysis of patterns of economic growth and transformation of economic sectors in medan city, The Province North Sumatera in 2012-2021 - Hasibuan*, Saidah Khairiyah; Sukardi, Sukardi; Tanjung, Ahmad Albar; Irsad, Irsad (Universitas Syiah Kuala, 2023)
This study uses secondary data with the methods are klassen typology analysis to determine the pattern and structure of the Medan City economy for North Sumatra Province, shift share analysis to review changes and the potential and contribution of the economic sector in 2012-2021. The results of this study include the city of Medan in type I, namely a prosperous area or a rapidly growing and advanced area where the rate of economic growth and income per capita are higher than those of its larger national area, namely the province of Sumatra North. The shift shares analysis results show that the construction, real estate, wholesale trade, education services, water supply, corporate services, industrial processing, financial services, and other services are positively competitive and high enough to become a sector that greatly contributes to the GRDP of Medan City in the transformation of the economic sectors shifted to the secondary sector. In the Medan City Economy, the LQ analysis shows that there are five leading sub-sectors: water supply, waste management, waste, and recycling; buying electricity and gas; health services and social activities; and corporate and other services.